Indirect signs of anterior cruciate ligament tear on MRI knee: a retrospective study - Sandhir, Gagan; Rahman, Shakilur (International Journal of Research in Medical Sciences, 2023)
Background: Anterior cruciate ligament is the most common ligament tear in knee and its primary role is to provide stability to the knee joint. Aim of study is to describe various secondary signs that are helpful in diagnosing partial/complete ACL tear. MRI offers distinct advantages over arthroscopy as a means of evaluating the ACL. MRI evaluation is effective in preventing unnecessary arthroscopy by assessing the severity of ACL tear and coexisting injuries. Methods: In this retrospective study 30 cases of partial/complete ACL tear were studied over a period of six months using Siemens Magnetom Essenza 1.5T MRI scanner in Srinivas institute of medical sciences and research centre, Mangalore. Results: To establish the sensitivity and specificity of indirect signs at MR imaging of Anterior Cruciate Ligament in 30 patients (18 with complete and 12 with partial thickness tear). The indirect signs were as follows: Bone Contusions (70%); Buckling of PCL (72%); Posterior displacement of lateral meniscus (54%); Anterior displacement of tibia (28%); pericruciate fat pad (86%); Wavy patellar tendon sign (28%) and associated joint effusion (90%). Conclusions: ACL ligament is the most commonly disrupted ligament in knee seen in radiology and orthopedic practice. A significant percentage of partial tears will progress to a functionally complete ACL tear. MRI helps guide the treatment decision process by demonstrating the extent of ACL injury and secondary signs make the accuracy of diagnosis stronger.